Impact of the self-healing agent composition on material characteristics of bio-based self-healing concrete - Hana Schreiberová; Petr Bílý; Josef Fládr; Karel Šeps; Roman Chylík; Tomáš Trtík (Case Studies in Construction Materials, 2019)
This paper investigates the composition of the biological self-healing agent based on its impact on material characteristics of concrete. A direct addition of the agent – a mixture of bacterial spores and nutrients – into concrete matrix has been investigated by many studies in recent decades. Under certain conditions, the applied microorganisms proved to be able to produce CaCO3, and researchers used this biocalcification process to autonomously seal microcracks in concrete. Thus, this bio-based material could potentially heal itself and lead to a more durable and economic structure. However, it has been shown that the self-healing agent, especially the indispensable nutrients, can positively or negatively influence the material characteristics. In this study, some of the most suitable and frequently proposed nutrients (calcium lactate, calcium nitrate, calcium formate, urea, and yeast extract) were directly added into cement mortar during the mixing process and their impact on material characteristics – compressive strength, flexural strength, and rheology – was evaluated and compared. Results show that calcium nitrate, calcium formate, calcium lactate, and urea have generally a potential to increase the compressive strength, especially in early ages. In contrast, the applied dose of yeast extract resulted in a drastic drop of compressive strength when compared to the control series, thus further optimization of the concentration is needed. The flexural strength was affected rather negligibly by the proposed nutritional admixtures. Keywords: Bio-based concrete, Self-healing concrete, Nutrients, Mechanical properties